A three-dimensional metal-based lithium-philic current collector, lithium metal anode and lithium metal battery
By using a three-dimensional metal-based lithium-philic current collector on the lithium metal negative electrode, including a three-dimensional metal substrate with an ordered porous structure and a nano-silver particle layer, the problem of the lithium metal negative electrode destroying the solid electrolyte interface layer due to volume changes during charging/discharging is solved, and the stable improvement of battery performance and dendrite suppression is achieved.
Patent Information
- Application Number
- CN202211740969.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-30
AI Technical Summary
As the negative electrode, lithium metal destroys the solid electrolyte interface layer due to volume changes during charging/discharging, resulting in sharp attenuation of battery performance and may cause dendrite formation and short-circuit failure.
A three-dimensional metal-based lithium-philic current collector is used, including a three-dimensional metal substrate with an ordered porous structure and a nano-silver particle layer generated by low-temperature ultrasonic assisted electroplating, as a modified layer for the lithium metal negative electrode.
This technical method can alleviate the stress effect during lithium deposition/peeling, reduce the lithium ion nucleation barrier, stabilize the solid electrolyte interface layer, extend the time of lithium ion depletion at the lithium metal interface, inhibit dendrites, and improve the cyclic stability and rate performance of the battery.
Smart Images

Figure CN115881973B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of negative electrode materials, and in particular to a three-dimensional metal-based lithium-philic current collector, a lithium metal negative electrode and a lithium metal battery. Background Art
[0002] Lithium metal as a negative electrode has a very high theoretical specific capacity (3860 mAh g -1 ), low density (0.53 g cm -3 ) and extremely low electrochemical potential (–3.04V vs standard hydrogen electrode), it is a very promising negative electrode material. However, thermodynamically unstable lithium metal reacts with the electrolyte to form a solid electrolyte interface layer (SEI). The SEI layer has the properties of electronic insulation and ion conductivity. The dense SEI layer can prevent the electrolyte from further decomposing, but the relatively infinite volume change of lithium metal during the charge / discharge process will destroy the fragile SEI layer, causing the electrolyte to further decompose, resulting in a sharp decline in battery performance, and the uneven distribution of lithium ions caused by the broken SEI will induce dendrite formation, leading to short-circuit failure of the battery. Therefore, there are still many problems to be solved if lithium metal batteries are to be put into practical use. Summary of the invention
[0003] In view of this, the present application provides a three-dimensional metal-based lithium-philic current collector, a lithium metal negative electrode and a lithium metal battery, so as to solve the problem of poor performance of lithium metal as a negative electrode in the prior art.
[0004] In a first aspect, the present application provides a three-dimensional metal-based lithium-philic current collector, comprising:
[0005] A three-dimensional metal substrate, wherein the three-dimensional metal substrate is an ordered porous structure;
[0006] The nano silver particle layer is in-situ generated on the surface of the three-dimensional metal substrate by low-temperature ultrasound-assisted chemical plating.
[0007] In a possible implementation, the three-dimensional metal substrate is any one of a copper mesh, a nickel mesh, and a stainless steel mesh.
[0008] In a possible implementation, the mesh size of the three-dimensional metal substrate is 100-400 mesh.
[0009] In a possible implementation, the thickness of the nanosilver particle layer is 50 to 500 nanometers; and the diameter of a single nanosilver particle in the nanosilver particle layer is 50 to 500 nanometers.
[0010] In a second aspect, the present application provides a method for preparing a three-dimensional metal-based lithium-philic current collector, comprising:
[0011] The silver source is dissolved in water and then mixed with a complexing agent, and then a stabilizer is slowly added to obtain a solution A, wherein the mass ratio of the silver source, the complexing agent and the stabilizer is 10:15-25:12-15;
[0012] The reducing agent and the dispersing agent are uniformly mixed and dissolved in water to obtain a solution B, wherein the mass ratio of the reducing agent to the dispersing agent is 1-5:15-10;
[0013] The solution A and the solution B are quickly mixed at a volume ratio of 1:2 to obtain a solution C;
[0014] Under low-temperature ultrasonic-assisted conditions, immersing the three-dimensional metal substrate in the solution C and allowing it to stand for 1 to 10 minutes to obtain the three-dimensional metal-based lithium-philic current collector according to any one of the first aspects;
[0015] Wherein, the temperature in the low-temperature ultrasonic auxiliary condition is 0-50°C, and the ultrasonic oscillation power is 10-100W.
[0016] In a possible implementation, the silver source is one or a combination of two or more of silver nitrate, silver fluoride and silver chlorate; the complexing agent is ammonia water; and the stabilizer is potassium hydroxide;
[0017] In a possible implementation, the reducing agent is one of citral and oxalic acid or a combination thereof; and the dispersing agent is acetone.
[0018] In a possible implementation, the reducing agent is a mixture of citral and oxalic acid in a mass ratio of 9:1 to 8:1.
[0019] In a third aspect, the present invention provides a lithium metal negative electrode, comprising: a three-dimensional metal-based lithium-philic current collector as described in any one of the first aspects; a surface area of the three-dimensional metal-based lithium-philic current collector is 0.5 to 2 mA cm -2 4-10 mAh cm is deposited at a current density of -2 of lithium metal.
[0020] In a fourth aspect, an embodiment of the present application provides a lithium metal battery, comprising: the lithium metal negative electrode described in the third aspect.
[0021] The three-dimensional metal-based lithium-philic current collector provided in the embodiment of the present application can not only alleviate the local accumulation of charges and the stress effect caused by volume expansion during lithium deposition / stripping, but also the ultrafine silver nanoparticles anchored on the three-dimensional metal substrate framework can significantly reduce the lithium ion nucleation barrier. In addition, the infinite solid solution effect and nano-size advantage of the lithium-silver alloy are utilized to greatly alleviate the negative impact of the peeling of the modified layer caused by stress. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0023] Figure 1 A schematic diagram of a process for preparing a three-dimensional metal-based lithium-philic current collector provided in this application;
[0024] Figure 2 The morphology of the current collectors of Example 1 and Comparative Example 1 provided in the present application;
[0025] Figure 3 The lithium metal deposition morphology of the current collectors of Example 1 and Comparative Example 1 provided in the present application;
[0026] Figure 4 Coulomb efficiency diagrams of three current collectors provided in Example 1, Comparative Example 1 and Comparative Example 2 of the present application;
[0027] Figure 5 A test diagram of a symmetrical battery assembled in Example 1 and Comparative Example 3 provided in the present application;
[0028] Figure 6 This is a rate performance test diagram of a full battery assembled with the lithium metal negative electrode and the lithium iron phosphate positive electrode obtained in Example 1 and Comparative Example 3 provided in the present application. DETAILED DESCRIPTION
[0029] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0030] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0031] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0032] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0033] In view of the problem of poor performance of lithium metal as negative electrode in the prior art, the applicant has found through research that due to the unique surface chemical properties and pore structure of the three-dimensional metal substrate framework, the composite lithium metal negative electrode can effectively reduce the local current density. According to the sand time's equation, this can prolong the time of lithium ion depletion at the negative electrode lithium metal interface and effectively inhibit the formation of dendrites. At the same time, the pore structure of the three-dimensional metal substrate framework provides space for the volume change produced during the lithium conversion reaction, alleviates the structural damage caused by volume expansion during lithium deposition / stripping, and stabilizes SEI. In addition, combined with surface lithium affinity modification, it can effectively reduce the lithium ion nucleation energy barrier and further homogenize the lithium ion flow, which is a modification method with great application prospects. The following is a detailed description in conjunction with the specific implementation method.
[0034] The embodiment of the present application provides a three-dimensional metal-based lithium-philic current collector, comprising: a three-dimensional metal substrate, the three-dimensional metal substrate is an ordered porous structure; a nanosilver particle layer, the nanosilver particle layer is in-situ generated on the surface of the three-dimensional metal substrate by low-temperature ultrasound-assisted chemical plating. It can be understood that the nanosilver particle layer is a modified layer of the three-dimensional metal substrate, and in other parts of this article, the three-dimensional metal-based lithium-philic current collector may also be referred to as a "modified current collector."
[0035] The ordered porous structure of the three-dimensional metal substrate can reduce the current density while regularizing the electric field distribution through the ordered structure. On the contrary, if a disordered porous structure is used, although the local current density can be reduced, the local electric field distribution is uneven due to the different pore sizes and shapes, and the problem of charge distribution is not fundamentally solved.
[0036] By introducing a uniformly distributed layer of nanosilver particles on a three-dimensional metal substrate, a lithium-silver alloy interface layer can be formed at the interface of the three-dimensional metal substrate, which reduces the nucleation energy barrier and promotes the diffusion of lithium ions, homogenizes the lithium ion flow, and guides the lateral growth of lithium metal along the substrate surface. On the contrary, if the surface of the three-dimensional metal-based lithium-philic current collector is lithium-phobic, the lithium ion nucleation barrier is high, which will cause lithium metal to preferentially nucleate and grow on the uneven substrate surface due to the tip discharge effect, resulting in dendrites.
[0037] By utilizing the infinite solid solution effect of lithium-silver alloy, the negative impact of the modified layer peeling off from the three-dimensional metal substrate surface due to stress and strain can be minimized, achieving stable interface modification. On the contrary, many lithium-philic modified layers in related technologies will peel off from the substrate surface due to stress and strain during the repeated deposition / stripping of lithium, thus losing their effectiveness.
[0038] In a possible implementation, the three-dimensional metal substrate is made of a material with good electrical conductivity. Specifically, the three-dimensional metal substrate can be any one of a copper mesh, a nickel mesh, and a stainless steel mesh.
[0039] In a possible implementation, the mesh size of the three-dimensional metal substrate is 100-400 mesh. For example, the mesh size is 100 mesh, 150 mesh, 200 mesh, 250 mesh or 400 mesh, and those skilled in the art can make an adaptive selection within this range according to actual needs. It should be pointed out that if the mesh size is too small, the specific surface area is limited, and the ability to alleviate the local aggregation of charges is limited; if the mesh size is too large, the pore size is too small, the effect of buffering volume expansion is weakened, and the number of side reaction sites increases.
[0040] In a possible implementation, the thickness of the nanosilver particle layer is 50 to 500 nanometers. For example, 50 nanometers, 100 nanometers, 150 nanometers, 200 nanometers, 250 nanometers, 300 nanometers, 350 nanometers, 400 nanometers, 450 nanometers, 500 nanometers, etc., and those skilled in the art can make adaptive selections within this range according to actual needs. It should be pointed out that if the thickness is too small, it cannot provide enough lithium-philic sites; if the thickness is too large, the cost is too high, and the impurities other than Ag increase.
[0041] In a possible implementation, the diameter of a single nanosilver particle in the nanosilver particle layer is 50 to 500 nanometers. For example, 50 nanometers, 100 nanometers, 150 nanometers, 200 nanometers, 250 nanometers, 300 nanometers, 350 nanometers, 400 nanometers, 450 nanometers, 500 nanometers, etc. Those skilled in the art can make adaptive selections within this range according to actual needs. It should be pointed out that if the diameter is too small, the Ag particles are highly active and easily oxidized and deteriorated; if the diameter is too large, the stress distribution is obviously uneven, and peeling is easy to occur.
[0042] In the embodiment of the present application, a three-dimensional metal substrate with a regularly distributed pore structure is selected, and a low-temperature ultrasound-assisted chemical plating method is used to in-situ grow an ultrafine nanosilver particle layer on its surface, so that the ultrafine nanosilver particles are evenly distributed on the inner and outer surfaces of the three-dimensional metal substrate as lithium-philic sites to control the reversible deposition / stripping of lithium metal. The lithium-silver alloy layer generated in situ during the electrochemical deposition process can effectively guide lithium ions to deposit uniformly along the surface of the mesh substrate, and thanks to the infinite solid solution effect and nano-size advantage of the lithium-silver alloy, the stress distribution of the modified layer is alleviated, so that the modified layer is firmly anchored to the substrate. The porous structure of the three-dimensional metal substrate provides a buffer space for the volume change during the deposition / stripping process of lithium metal, reducing the structural damage caused by internal stress. The synergistic effect of the two makes the generated SEI film dense and uniform, and has good stability. The lithium metal battery assembled using the lithium metal negative electrode exhibits good cycle stability and rate performance.
[0043] Corresponding to the above-mentioned three-dimensional metal-based lithium-philic current collector, the embodiment of the present application also provides a method for preparing a three-dimensional metal-based lithium-philic current collector.
[0044] See also Figure 1 , is a schematic diagram of a process for preparing a three-dimensional metal-based lithium-philic current collector provided in an embodiment of the present application. Figure 1 As shown, it mainly includes the following steps.
[0045] Step S101: dissolving the silver source in water and mixing it with the complexing agent, and then slowly adding a stabilizer to obtain solution A.
[0046] In a specific implementation, in order to make the silver nanoparticle layer grow better, it is necessary to control the amount of silver source, complexing agent and stabilizer. Therefore, in the embodiment of the present application, the mass ratio of silver source, complexing agent and stabilizer is preferably 10:15-25:12-15. For example, the mass ratio of silver source, complexing agent and stabilizer is 10:15:12, 10:20:12, 10:25:12, 10:15:13, 10:15:14, 10:15:15, 10:20:13, 10:20:14, 10:20:15, 10:25:13, 10:25:14, 10:25:15, etc. Those skilled in the art can make adaptive selections within this range according to actual needs. It should be pointed out that if there is too much complexing agent, the substrate cannot be plated, and if there is too little, the plating solution will decompose; if there is too much stabilizer, it will not be plated, and if there is too little, precipitation will occur.
[0047] In a possible implementation, the silver source is one or a combination of two or more of silver nitrate, silver fluoride and silver chlorate; the complexing agent is ammonia water; and the stabilizer is potassium hydroxide.
[0048] Step S102: uniformly mix the reducing agent and the dispersing agent and dissolve them in water to obtain a solution B.
[0049] In a specific implementation, the mass ratio of the reducing agent to the dispersant is 1-5:15-10. For example, the mass ratio of the reducing agent to the dispersant is 1:15, 2:15, 3:15, 5:15, 1:13, 2:13, 3:13, 5:13, 1:10, 2:10, 3:10, 5:10, etc., and those skilled in the art can make adaptive selections within this range according to actual needs. It should be pointed out that if there is too much reducing agent, it is easy to produce automatic precipitation of Ag particles after mixing with solution A, and if there is too little, the chemical plating effect is not good; if there is too much dispersant, the reducing agent is diluted, the chemical plating effect is not good, and if there is too little dispersant, the reducing agent cannot be evenly dispersed.
[0050] In a possible implementation, the reducing agent is one of citral and oxalic acid or a combination thereof; the dispersant is acetone. Preferably, the reducing agent is a mixture of citral and oxalic acid in a mass ratio of 9:1 to 8:1. It should be noted that if there is too much citral, it is difficult to mix, and if there is too little, the reducing property is weakened; if there is too much oxalic acid, it is difficult to mix, and if there is too little, the reducing property is weakened.
[0051] Step S103: Rapidly mix solution A and solution B at a volume ratio of 1:2 to obtain solution C.
[0052] Step S104: Under low-temperature ultrasonic-assisted conditions, immerse the three-dimensional metal substrate in solution C and allow it to stand to obtain a three-dimensional metal-based lithium-philic current collector.
[0053] It can be understood that in this step, "immersing the three-dimensional metal substrate in solution C and allowing it to stand under low-temperature ultrasonic-assisted conditions" means performing chemical plating treatment under low-temperature ultrasonic-assisted conditions.
[0054] In a specific implementation, the treatment temperature of chemical plating is 0 to 50°C, such as 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, etc. Those skilled in the art can make an adaptive selection within this range according to actual needs. It should be pointed out that if the temperature is too low, the chemical plating reaction time is too long, and if the temperature is too high, the components of the plating solution volatilize and the plating solution becomes ineffective.
[0055] The treatment time of chemical plating is 1-10 minutes, for example, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes, etc. Those skilled in the art can make an adaptive selection within this range according to actual needs. It should be pointed out that if the immersion time is too short, the amount of Ag plated is too small, and the effect of improving the lithium affinity is poor. If the immersion time is too long, the amount of miscellaneous substances other than Ag increases, and the side reactions increase.
[0056] The ultrasonic power is 10-100W, and the frequency is 40Hz, such as 10W, 20W, 30W, 40W, 50W, 60W, 70W, 80W, 90W or 100W, etc. Those skilled in the art can make an adaptive selection within this range according to actual needs. It should be pointed out that if the ultrasonic oscillation power is too low, the chemically plated Ag particles are prone to agglomeration, and if it is too high, chemical plating cannot be carried out.
[0057] In the embodiment of the present application, the ultrasonic assisted method is used to provide more nucleation energy for the silver ions to nucleate on the substrate, and on the other hand, the ultrasonic vibration is used to suppress the rapid growth and agglomeration of the nucleated silver crystals, and finally a uniformly dispersed fine silver nanoparticle layer is formed on the surface of the substrate. On the contrary, if the traditional chemical plating method is used, the diameter of the finally formed coating particles is large and it is easy to agglomerate, making it easier for the stress distribution on the particle surface to be uneven, thereby causing the coating to fall off, which is not conducive to guiding the uniform deposition of lithium.
[0058] Corresponding to the above embodiment, the embodiment of the present application further provides a lithium metal negative electrode, which includes the three-dimensional metal-based lithium-philic current collector described in the above embodiment; the surface of the three-dimensional metal-based lithium-philic current collector is 0.5-2 mA cm -2 4-10 mAh cm was deposited at a current density of -2 For example, the surface of the three-dimensional metal-based lithium-philic current collector is 1 mA cm -2 8 mAh cm was deposited at a current density of -2 of lithium metal. It can be understood that after lithium metal is deposited on the surface of the three-dimensional metal-based lithium-philic current collector, a lithium-silver alloy interface layer is formed at the interface of the three-dimensional metal substrate. It should be pointed out that if the deposition current density is too large, lithium dendrites are easily generated. If it is too small, it takes too long and the side reactions are more obvious. If the amount of deposited lithium is too much, the substrate pores are completely filled, and the buffer volume expansion capacity is weakened. If it is too little, the amount of negative electrode lithium is insufficient to support the battery for long-term cycling.
[0059] Corresponding to the above embodiment, the embodiment of the present application further provides a lithium metal battery, which includes the lithium metal negative electrode described in the above embodiment.
[0060] For ease of understanding, the technical solution provided in this application is described in detail below in conjunction with specific embodiments.
[0061] Example 1
[0062] (1) 3.4 g of silver nitrate and 6.8 g of aqueous ammonia were added to 70 mL of deionized water under magnetic stirring and mixed thoroughly, and then 3.4 g of sodium hydroxide was slowly added thereto to obtain solution A.
[0063] (2) Add 9 g of citral, 1 g of oxalic acid, and 130 g of acetone to 220 mL of deionized water and mix thoroughly to obtain solution B.
[0064] (3) rapidly mixing solution A and solution B at a volume ratio of 1:2 to obtain a colorless and transparent solution C;
[0065] (4) The cleaned 400-mesh copper mesh was immersed in solution C for 2 min at 5 °C and 60 W ultrasonic power. Subsequently, the modified three-dimensional metal-based lithium-philic current collector was obtained by washing and drying, which was labeled as Cu mesh@Ag.
[0066] Example 2
[0067] The difference from Example 1 is that the chemical plating time in Example 2 is 1 min, and the rest is the same as Example 1 and will not be repeated here.
[0068] Example 3
[0069] The difference from Example 1 is that the chemical plating time in Example 3 is 3 min, and the rest is the same as Example 1 and will not be repeated here.
[0070] Example 4
[0071] The difference from Example 1 is that the ultrasonic power of Example 4 is 70W, and the rest is the same as Example 1 and will not be repeated here.
[0072] Example 5
[0073] The difference from Example 1 is that the ultrasonic power of Example 5 is 90W, and the rest is the same as Example 1 and will not be repeated here.
[0074] Example 6
[0075] The difference from Example 1 is that the silver source in Example 6 is silver fluoride, and the rest is the same as Example 1 and will not be repeated here.
[0076] Example 7
[0077] The difference from Example 1 is that the silver source in Example 7 is silver chlorate, and the rest is the same as Example 1 and will not be repeated here.
[0078] Comparative Example 1
[0079] The difference from Example 1 is that the copper mesh in Comparative Example 1 is a cleaned copper mesh, which is a blank current collector and is marked as Cu mesh. The specific preparation process is: the copper mesh is cleaned with acetone, ethanol, and deionized water in sequence and then dried.
[0080] Comparative Example 2
[0081] Different from Example 1, Comparative Example 2 uses copper foil as a blank negative electrode, which is marked as Cu foil.
[0082] Comparative Example 3
[0083] Different from Example 1, Comparative Example 3 uses lithium foil as a blank negative electrode, which is marked as Bare Li.
[0084] Test Example 1
[0085] The morphology of the three-dimensional metal-based lithium-philic current collector prepared in Example 1 and the blank current collector in the comparative example was characterized. Figure 2 As shown. Among them, a and c are scanning electron microscope images of the copper mesh substrate shown in Comparative Example 1; b and d are scanning electron microscope images of the three-dimensional metal-based lithium-philic current collector shown in Example 1. Figure 2 It can be seen that the diameters of the holes in the blank copper mesh substrate and the single copper wire are about 95μm and 45μm respectively. In the three-dimensional metal-based lithium-philic current collector, ultrafine silver nanoparticles are evenly distributed on the surface of the copper mesh, with a particle diameter of 50 to 100nm.
[0086] Test Example 2
[0087] The three-dimensional metal-based lithium-philic current collector prepared in Example 1 was used to assemble a half-cell to test the morphology of lithium metal deposition on the current collector. In the assembled half-cell system, the metal lithium foil was used as the negative electrode and the three-dimensional current collector was used as the positive electrode. The battery was encapsulated in an argon atmosphere glove box. The assembled battery was charged at 1 mA cm -2 Lithium metal deposition was performed at a current density of . The current collector after lithium metal deposition was washed and dried with the corresponding electrolyte solvent, and then sealed and transferred to a scanning electron microscope for morphology testing. The test results are shown in Figure 3 As shown. Among them, a is a scanning electron microscope image of lithium metal deposited on a three-dimensional metal-based lithium-philic current collector; b is a scanning electron microscope image of lithium metal deposited on a copper mesh substrate. Figure 3 It can be seen that the ultrafine silver nanoparticles on the surface of the three-dimensional metal-based lithium-philic current collector can guide lithium ions to nucleate and deposit uniformly on the surface of the copper mesh, and no lithium dendrites are generated on the surface, indicating that the three-dimensional metal-based lithium-philic current collector effectively stabilizes the lithium metal negative electrode interface.
[0088] Test Example 3
[0089] The coulombic efficiency of the lithium sheet assembled half-cells of Example 1 and Comparative Example 1 and Comparative Example 2 was tested respectively, and the current density was 1 mA cm -2 , the amount of lithium deposited / stripped is 1 mAh cm -2 The test results are shown in Figure 4 and Table 1.
[0090] Table 1 Coulombic efficiency test of three-dimensional metal-based lithium-philic current collector half-cell
[0091]
[0092]
[0093] Depend on Figure 4 As can be seen from Table 1, the Coulombic efficiency and cycle life of the three-dimensional metal-based lithium-philic current collector are significantly improved.
[0094] Test Example 4
[0095] This test example compares the cycle stability test of the symmetrical battery assembled in Example 1 and Comparative Example 3. First, in the half-cell, a metal-based three-dimensional lithium-philic current collector is preliminarily charged at 0.5 mA cm -2 8 mAh cm was deposited at a current density of -2 The composite lithium metal anode was prepared from lithium metal, and the composite lithium metal anode was cleaned and dried and assembled into a symmetrical battery for testing with a current density of 1 mA cm -2 , the amount of lithium deposited / stripped is 1 mAh cm -2 The results are as follows Figure 5 And as shown in Table 2.
[0096] Table 2 Symmetrical battery test of three-dimensional metal-based lithium-philic current collector
[0097]
[0098] Depend on Figure 5 As can be seen from Table 2, the cycle stability of the modified lithium metal composite negative electrode is increased and the voltage polarization is reduced, indicating that the lithium ion transport performance and structural stability of the three-dimensional metal-based lithium-philic current collector are enhanced.
[0099] Test Example 5
[0100] The lithium metal composite negative electrode based on the modified current collector prepared in Test Example 4 was matched with the lithium iron phosphate positive electrode to assemble a lithium iron phosphate-lithium metal full battery, and the capacity at 0.2C, 0.5C, 1C, 2C, 3C, 5C, and 1C rates was tested. The test results are as follows Figure 6 As shown. Figure 6 It can be seen that the lithium iron phosphate full battery assembled using the lithium metal negative electrode prepared in the embodiment of the present application has a higher capacity than that of Comparative Example 3 at different rates.
[0101] In summary, compared with the prior art, the three-dimensional metal-based lithium-philic current collector provided by the embodiment of the present application can not only alleviate the local accumulation of charges and the stress effect caused by volume expansion during lithium deposition / stripping, but also the ultrafine silver nanoparticles anchored on the three-dimensional metal substrate framework can significantly reduce the lithium ion nucleation barrier. In addition, the infinite solid solution effect and nano-size advantage of lithium-silver alloy are utilized to greatly alleviate the negative impact of the peeling of the modified layer caused by stress, and the preparation method is simple and easy to mass produce, which has great potential in practical applications.
[0102] The above is only a specific implementation of the present application. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. The protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A three-dimensional metal-based lithium-philic current collector, characterized in that: include: A three-dimensional metal substrate, wherein the three-dimensional metal substrate is an ordered porous structure; A nanosilver particle layer, wherein the nanosilver particle layer is in-situ generated on the surface of the three-dimensional metal substrate by low-temperature ultrasound-assisted chemical plating; The three-dimensional metal substrate is any one of a copper mesh, a nickel mesh, and a stainless steel mesh; The mesh size of the three-dimensional metal substrate is 100-400 mesh; The thickness of the nanosilver particle layer is 50 to 500 nanometers; the diameter of a single nanosilver particle in the nanosilver particle layer is 50 to 100 nanometers; The preparation method of the three-dimensional metal-based lithium-philic current collector comprises: The silver source is dissolved in water and then mixed with a complexing agent, and then a stabilizer is slowly added to obtain a solution A, wherein the mass ratio of the silver source, the complexing agent and the stabilizer is 10:15-25:12-15; The reducing agent and the dispersing agent are uniformly mixed and dissolved in water to obtain a solution B, wherein the mass ratio of the reducing agent to the dispersing agent is 1-5:15-10; The solution A and the solution B are quickly mixed at a volume ratio of 1:2 to obtain a solution C; Under low-temperature ultrasonic-assisted conditions, immersing the three-dimensional metal substrate in the solution C and allowing it to stand for 1 to 10 minutes to obtain the three-dimensional metal-based lithium-philic current collector; The temperature of the low-temperature ultrasonic auxiliary condition is 0-50°C, and the ultrasonic oscillation power is 10-100 W; The silver source is one or a combination of two or more of silver nitrate, silver fluoride and silver chlorate; the complexing agent is ammonia water; and the stabilizer is potassium hydroxide; The reducing agent is one of citral and oxalic acid or a combination thereof; the dispersing agent is acetone.
2. The three-dimensional metal-based lithium-philic current collector according to claim 1, characterized in that: The reducing agent is a mixture of citral and oxalic acid in a mass ratio of 9:1 to 8:
1.
3. A lithium metal negative electrode, characterized in that include: The three-dimensional metal-based lithium-philic current collector according to claim 1; The surface of the three-dimensional metal-based lithium-philic current collector is 0.5-2 mA cm -2 The deposition current density was 4-10 mAh cm -2 of lithium metal.
4. A lithium metal battery, characterized in that: include: The lithium metal negative electrode according to claim 3.